Effects of Emotion Regulation Skills on Abstinence after Inpatient Treatment for Alcohol Use Disorder: A Latent Difference Score Analysis - Rupp, Lydia; Saur, Sebastian; Berking, Matthias (3. Deutscher Psychotherapiekongress (DPK), 2024)
Theoretischer Hintergrund: Alcohol use disorder (AUD) is a debilitating mental health problem, frequently developing into a chronic disorder (McKay & Hiller-Sturmhofel, 2011). While behavioral and cognitive treatments have been proven to be effective treatment approaches (Witkiewitz et al., 2019), barriers to adequate aftercare may increase risk for relapse and, thus, chronic development of the disorder (Buchholz et al., 2019). Therefore, understanding the mechanisms contributing to relapse risk may inform the development of effective aftercare and prevention strategies. A promising factor are emotion regulation skills, which have been shown to predict abstinence after psychotherapy for AUD (Berking et al., 2012). Fragestellung: Can emotion regulation skills predict abstinence in individuals with AUD after inpatient treatment? Methoden: We will use data of n = 356 individuals with AUD from a large randomized controlled trial on aftercare after inpatient treatment for AUD (Saur et al., 2022). AUD was diagnosed using the Structured Clinical Interview for DSM-5 Disorders-Clinician Version (First et al., 2016). Emotion regulation skills were assessed with the German version of the Emotion Regulation Skills Questionnaire (Berking & Znoj, 2008). Relapse and abstinence were assessed with the Timeline Follow-Back Alcohol interview (Sobell & Sobell, 1992). Outcomes were assessed before aftercare treatment (T1), mind-intervention (T2), six weeks after randomization (T3), and three (T4) and six months after randomization (T5). Data will be analysed using a Latent Difference Score approach (Hamagami & McArdle, 2001) to assess effects of emotion regulation skills on abstinence over time. Ergebnisse: Data analysis is underway and results will be presented. Diskussion: This analysis will build on and extend previous findings on the effects of emotion regulation skills on abstinence (Berking et al., 2012). We will replicate the results using a larger sample and a different analysis approach. The findings may help to develop more tailored and effective strategies for relapse prevention in AUD. This study addresses the limitations of the previous study (Berking et al., 2012) by including an untreated control group and using a standardized clinical interview for the diagnosis of AUD